Farmers access to agricultural inputs and services in Nigeria: panacea to competitive and sustainable cassava production and agro-enterprise development - Asumugha, G.N.; Tarawali, G.; Dixon, Alfred G.O. (International Institute of Tropical Agriculture, 2010)
The critical role that agricultural inputs play in the modernization and competitiveness of the agriculture sector cannot be overemphasized. Inputs that have been identified as critical to commercial cassava enterprise include fertilizer, tractor hiring services, fabricators of various equipment for processing raw materials, credit support, crop protection products (Agrochemicals) and processors of these products. The principal emphasis of the cassava enterprise development project (CEDP) in Nigeria is to support economic opportunities through sustainable and competitive cassava production, marketing and agro-enterprise development. The present study aims at identifying and facilitating farmers/producers groups’ access to inputs, credit, and technologies (fertilizer, agrochemicals, tractor services, appropriate machines, etc.) to support cassava production and enterprise development. Data were gathered through primary as well as secondary sources. The initial literature and desk review guided information from records and present situations in agricultural input provision. Records of States Agricultural Development Programmes, States’ ministries of agriculture and organizations involved in input supplies and distribution were looked into and their staff interviewed to establish background for current practices. A rapid appraisal survey was then conducted using key dealers of these inputs to obtain information on input supplies and distribution. Interviews covered major participants in the twelve CEDP States in the Niger Delta areas (South-East and South-South geo-political zones) of Nigeria. The inputs and service delivery ascertained from this study was far from being ideal. However, there were some modest efforts of some of the States in some aspects of inputs and service provision. It is recommended that States’ agencies responsible for inputs procurement and distribution be put in place to avoid the bureaucracies of government outfits in discharging agricultural input distribution.